Nanocellulose crystals derivative-silica hybrid sol open tubular capillary column for enantioseparation. (1st June 2017) - Dong, Shuqing; Sun, Yaming; Zhang, Xia; Li, Hui; Luo, Guoying; Zhao, Liang
Highlights: Nanocellulose crystals derivative-silica hybrid sol layer-by-layer self-assembly method for coating fabrication. Thirteen different enantiomers have been successful separated. Longer column life, better repeatability and higher stability for the capillary column. Abstract: Broad spectrum separation of chiral compounds is a challenge task for analysts. It is significant for preparation of chiral stationary phase and selection of separation technology in the field. Here, we present a novel nanocellulose crystals (NCCs) which were derivation with 3, 5-dimethylphenyl isocynate (DMPC) and silane with 3-triethoxysilylpropylisocyanate form sol in tetraethylorthosilicate (TEOS) and layer-by-layer self-assembly in the inner of capillary to fabricate the organic-inorganic hybrid open tubular capillary column (DMPC/NCCs-OTC) for enantiomers separation by capillary electrochromatography technology (CEC). The experimental results verified that this coating column has the broad spectrum separation ability and high resolution efficiency for thirteen different enantiomers at the optimal CEC conditions. The mechanizations of DMPC/NCCs-OTC modified layer numbers and structure effect on chiral separation performance have been investigated and compared. Although the limitation and difficulty in fabrication of open tubular coating column, this work provided the preparation method of stability, controlled, long column life, adequate repeatability and satisfied enantioseparation performance.